Trace Metal Availability Affects Greenhouse Gas Emissions and Microbial Functional Group Abundance in Freshwater Wetland Sediments - Giannopoulos, Georgios; Hartop, Katherine R.; Brown, Bonnie L.; Song, Bongkeun; Elsgaard, Lars; Franklin, Rima B. (Frontiers in Microbiology, 2020)
We investigated the effects of trace metal additions on microbial nitrogen (N) and carbon (C) cycling using freshwater wetland sediment microcosms amended with micromolar concentrations of copper (Cu), molybdenum (Mo), iron (Fe), and all combinations thereof. In addition to monitoring inorganic N transformations (NO3-, NO2-, N2O, NH4+) and carbon mineralization (CO2, CH4), we tracked changes in functional gene abundance associated with denitrification (nirS, nirK, nosZ), dissimilatory nitrate reduction to ammonium (DNRA; nrfA), and methanogenesis (mcrA). Greater availability of Cu led to more complete denitrification (i.e., less N2O accumulation) and a higher abundance of the nirK and nosZ genes, which encode for Cu-dependent reductases. We found sparse evidence of DNRA activity and no consistent effect of the trace metal additions on CO2 production. In contrast, net CH4 production was stimulated by the amendments, and Mo additions led to increased mcrA gene abundance. These findings demonstrate that trace metal effects on sediment microbial physiology can impact community-level function. We observed direct and indirect effects on both N and C biogeochemistry that resulted in increased production of greenhouse gasses, which may have been mediated through the documented changes in microbial community composition and shifts in functional group abundance. Overall, this work supports a more nuanced consideration of metal effects on environmental microbial communities that recognizes the key role that metal limitation plays in microbial physiology.